Choumiryou dan Harapan Hidup Orang Jepang - Sriwahyu Istana Trahutami (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
The life expectancy of Japanese is the highest in the world, an average of 83 - 84 years. This makes Japan a world role model in order to be able to live long and healthy lives. Many factors influence the high life expectancy of Japanese, one of which is food. Japanese food or washoku (和 食) has already become widely known and widely accepted. Along with this, Japanese basic ingredients or choumiryou (調味 料) are becoming well known. The purpose of this study is to describe the influence of choumiryou on the high life expectancy of Japanese. This study used descriptive qualitative method. The results of this study indicate that basic choumiryou has a large influence on the health of Japanese people. Although some basic spices are not good for health, this does not prevent Japanese from consuming them. Japanese consume choumiryou in a safe portion that does not damage health. In addition, the role of the basic choumiryou in the high life expectancy of Japanese people can also be seen from various kinds of substances that are good for health contained in the basic sashisuseso choumiryou. The taste of choumiryou has always been maintained by the Japanese for the sake of acquiring a distinctive Japanese flavor that has a characteristic soft taste.